Climate Change Scenarios for Southeast Asia and Vietnam: Current Status and Future Research Directions - Duc Thanh, Ngo (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 1, 2023)
Abstract: This paper presents a comprehensive review of  the development of climate change scenarios (CC) in Southeast Asia and Vietnam over the past decades. In Southeast Asia, the dynamical downscaling approach using regional climate models has been mainly applied, especially by the Coordinated Regional Climate Downscaling Experiment - Southeast Asia (CORDEX-SEA) community. In Vietnam, climate change scenarios were published and updated in 2009, 2012, 2016, and, most recently, in 2020 by the Ministry of Natural Resources and Environment. While recent CC scenarios in Vietnam have favored the dynamical approach, some studies have already applied the statistical method and performed the downscaling for multiple models and greenhouse gas (GHG) scenarios. So far, experiments in the region and Vietnam have only focused on downscaling results from global climate models participating in the Coupled Model Intercomparison Project Phase 3 (CMIP3) and Phase 5 (CMIP5). Published results show a consensus on the increase in projected temperature; however, the results of precipitation projections remain highly uncertain. This paper subsequently proposes several research directions that could be implemented in the coming years in the region, including: i) Building a high-resolution grid-based climate dataset; ii) Downscaling CMIP6 products with the latest GHG scenarios using dynamical, statistical, and probabilistic projections, with a focus on the role of urbanization in the context of global climate change; and iii) Developing a regional coupled atmosphere-ocean system to better understand the mechanism of future climate change in the region and Vietnam. Keywords: Climate change, downscaling, future scenarios, Southeast Asia, Vietnam.